Implementasi Program Kampus Mengajar dalam Meningkatkan Literasi dan Numerasi Siswa di SMK - Khansa Hafidza; Kundharu Saddhono; Ani Rakhmawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to implement the Class 7 teaching campus program in improving student literacy and numeracy at Bhakti Karya Simo Vocational School. The method used is a qualitative descriptive method with an interpretive paradigm because the researcher is directly involved in the interaction. Data collection techniques through observation, interviews and case studies. The objects of this research are schools, students and students' learning activities during campus teaching assignments. This research was carried out for almost four months, starting from February 26 to June 2 2024. The results of this research are that the campus teaching program carries out various work programs that can improve students' literacy and numeracy skills, such as literacy habits, library viewing, literacy corners, magazines wall, work language week, literacy and numeracy festival, numeracy snakes and ladders, numeracy crossword puzzle, mathematics quiz, technology adaptation training to natural disaster mitigation adaptation. In its implementation, there are various obstacles and challenges faced by students, but they can be resolved by finding the best solution.